Efficacy of dynamic visuo-attentional interventions for reading in dyslexic and neurotypical children: A systematic review. (May 2019) - Peters, Jessica L.; De Losa, Lauren; Bavin, Edith L.; Crewther, Sheila G.
Highlights: Visuo-attentional interventions improve reading outcomes in dyslexic children. Improvements are equal or greater than other options and last at least two months. Visual perceptual trainings can benefit reading fluency and comprehension. Visually-based reading acceleration programs can improve reading accuracy and rate. Action video games can increase reading rate and fluency. Abstract: Dyslexia is associated with phonological and visuo-attentional deficits. Phonological interventions improve word accuracy and letter-sound knowledge, but not reading fluency. This systematic review evaluated the effectiveness of dynamic computerized visuo-attentional interventions aimed at improving reading for dyslexic and neurotypical children aged 5–15. Literature searches in Medline, PsycINFO, EMBASE, Scopus, ERIC, PubMed, Web of Science, and Cochrane Library identified 1266 unique articles, of which 18 met inclusion criteria (620 participants; 91.40% dyslexic). Three types of visuo-attentional interventions were identified. Results show that visual perceptual training ( n  = 5) benefited reading fluency and comprehension, visually-based reading acceleration programs ( n  = 8) improved reading accuracy and rate, and action video games ( n  = 5) increased rate and fluency. Visuo-attentional interventions are effective options for treating childhood dyslexia, improving reading generally equal to or greater than other strategies. Initial evidence indicates that visuo-attentional interventions may be efficacious in different orthographies, and improve reading for at least two months after intervention. Larger sample interventions on a wider range of reading skills with follow-up assessment are needed to further clarify their effectiveness.